Youth and consumption: Analytical frameworks for problematizationCONSUMPTION: ANALYTICAL FRAMEWORKS FOR PROBLEMATIZATION - Catalán Marín, Omar (Última Década, 2020)
This presents a basic conceptual framework that addresses the processes of consumption among youth from a relational perspective. It comes in the first instance as a macro-social context that defines societies with a consumer culture and its relationship with youth. Subsequently it develops a set of psychosocial and cultural elements of consumption for further analysis. Eventually it develops a relational presentation of the conceptual elements to guide the interpretation of consumption in youth within a specific social context, that is, within consumer societies.